Entre a expectativa e a realidade: implicações do Plano de Expansão e Reestruturação das Universidades Federais (REUNI) para a formação acadêmico- profissional em Serviço Social no contexto da Universidade Federal de Campina Grande, Campus Sousa - PB - Lima, Doniêgo Ferreira de (2020)
This dissertation deals with the theme of the Interiorization of Undergraduate Courses, through the Plan of Expansion and Restructuring of Federal Universities (REUNI). Its central scope was to analyze the implications for academic-professional training in Social Work with the expansion of Undergraduate Courses, through REUNI, in reality at the Federal University of Campina Grande - PB (UFCG), Campus Sousa - PB. It is worth mentioning that the research had as specific objectives to apprehend REUNI's objectives, principles, guidelines, methodology and schedule; detect what are the possibilities and challenges for the realization of the training project expressed in the Curriculum Guidelines of 1996, in the Social Service Course, Campus Sousa - PB. To this end, historical-dialectical materialism seemed to us to be the most viable theoretical-methodological support for undertaking a concrete analysis of the concrete reality, that is, to critically capture the contradictions that go through the process of professional training. In order to be able to meet the research objectives, we opted to invest in a documentary research, analyzing the Political Pedagogical Plan of the Course, the proposal to join UFCG to REUNI, the minutes of the collegiate meeting in which the proposal was approved, etc. This critical-analytical path provided elements that brought us closer to the reality of our object of study, whose relevance lies precisely in the possibility of systematizing the particularities that involve academic-professional training in Social Work in Alto Sertão Paraibano, highlighting the implications of REUNI for this training, in addition to being, to a large extent, a contribution to the professional debate, above all, in relation to the quality of the training process, the conditions of the teaching work and the challenges and possibility for the implementation of the Curricular Guidelines of the Brazilian Association of Education and Research in Social Work (ABEPSS). In this perspective, research is also an invitation to strengthen the collective struggle in defense of public, secular, free and quality education. The research recognized the importance of the process of interiorization of higher education, identified a set of efforts by the faculty of the UFCG Social Service course to develop quality academic-professional training, based on the ABEPSS Curricular Guidelines and concluded that some of the proposals of REUNI have not taken place, which has made work precarious, considering, for example, the increase in students at the expense of expanding the staff and investments in campus infrastructure.